STUDY OF CARRIER RATE OF COVID-19 AMONG PARACLINICAL and GOVERNMENT DEGREE COLLEGE STUDENTS AT A TERTIARY CARE HOSPITAL, SRIKAKULAM - BHARATHI, M.; BADAMPUDI, S. S. VIJAYASRI (International Journal of Current Pharmaceutical Research, 2023)
Objective: Role of nosocomial transmission of SARS-CoV-2 is becoming increasingly recognized, with several reports indicating that the number of asymptomatic cases can be several-fold higher than the reported symptomatic cases. With this background, we did study to know the carrier rate of Covid-19 in healthy, asymptomatic adolescents and young adults and to compare it among students exposed and not exposed to healthcare settings. Methods: Nasopharyngeal swabs were collected from 200 students: DMLT trainees as test group and Degree college students as control group, in equal number. Samples were subjected to RT-PCR test for Covid-19, by extracting RNA by using the "HimediaHiGenoMB" kit and doing PCR by using "Meril Covid-19 one-step RT-PCR kit. Results: All the participants are in the age group of 18-22 y and Female students constituted 73.5%. All participants in the test group were vaccinated (100%), but only 34% in control group (94.4% of female and 64.28% of male students had two doses). One-fourth of male students were not vaccinated at all in control group. None of the control group were positive for covid-19, but four male students (16%) and 11 female students (14.6%) were positive in test group. Conclusion: Healthcare professionals (HCPs) are at risk of getting infection of Covid 19, because of their exposure to asymptomatic or, pre-symptomatic or to the Covid-19 positive persons before the diagnosis being made. Vaccine coverage in male students was less when compared to female students. Hundred percent vaccine coverage was seen in HCPs.